"Jamaah" As a Communication Symbol of Da’wah of Wahdah Islamiyah Group - Hasanah, Uswatun (Palakka : Media and Islamic Communication, 2020)
Wahdah Islamiyyah is a religious group that has its own characteristics. Its main strength lies in the concept of 'Jamaah' as well as its group doctrine. As a dakwah concept, the term 'Jamaah' has a meaning manifested in the behavior of each of his followers. Therefore, this study aims to reveal the meaning of 'Jamaah' as religious propaganda. The unit of analysis of this study was the followers of the Wahdah Islamiyyah group. Thus, this research approach is a case study. Data were collected by in-depth interview techniques, observation, and literature review. Furthermore, the data were analyzed using the Three-Groove Technique model in the form of reduction, categorization, and interpretation as a result. The results of this study are: (1) Wahdah Islamiyyah (WI) has the power as a 'Jamaah' (community) which is also a symbol of communication. Through the 'pilgrims' they display their identity as a form of dakwah. (2) 'Jamaah' is also a social relationship which has the function of strengthening individual relations by means of emotional ties and social solidarity. The conclusion of this research is Wahdah Islamiyyah has the identity (characteristic) of 'Jamaah' with all its elements which is an attraction to others as a symbol of communication.